Critically coupled silicon Fabry-Perot photodetectors based on the internal photoemission effect at 1550 nm - Casalino, Maurizio; Coppola, Giuseppe; Iodice, Mario; Rendina, Ivo; Sirleto, Luigi (Optics express, 2012)
In this paper, design, fabrication and characterization of an all-silicon photodetector (PD) at 1550 nm, have been reported. Our device is a surface-illuminated PD constituted by a Fabry-Perot microcavity incorporating a Cu/p-Si Schottky diode. Its absorption mechanism, based on the internal photoemission effect (IPE), has been enhanced by critical coupling condition. Our experimental findings prove a peak responsivity of 0.063 mA/W, which is the highest value obtained in a surface-illuminated IPE-based Si PD around 1550 nm. Finally, device capacitance measurements have been carried out demonstrating a capacitance < 5 pF which has the potential for GHz operation subject to a reduction of the series resistance of the ohmic contact.